Front Cover: Advanced Cell Mapping Visualizations for Single Cell Functional Proteomics Enabling Patient Stratification. Issue 13 (6th July 2020) - Bowman, Nick; Liu, Dong; Paczkowski, Patrick; Chen, Jon; Rossi, John; Mackay, Sean; Bot, Adrian; Zhou, Jing
Abstract : DOI: 10.1002/pmic.201900270 In article number 1900270, Bowman et al. discuss state‐of‐the‐art data visualization platforms used to address the increasing challenges of identifying immune cell subset clinical biomarkers in oncology, from high dimensional single‐cell data. Next generation algorithms integrated into the IsoSpeak software suite transform complex, multi‐dimensional single‐cell proteomic data into intuitive graphical representations, such as the stylized 3D UMAP and 3D t‐SNE featured on this cover, and additionally polyfunctional heatmaps and PAT‐PCA, to simplify complex underlying biological systems and their interactions.